Implikasi Perbedaan Klasifikasi AWaRe WHO Dan Kemenkes RI Terhadap Evaluasi Penggunaan Antibiotik: Tinjauan Literatur - Yusna Fadliyyah Apriyanti; Reza Rahmawati; Muthia Nurhidayah; Baha Udin (Poltekkes Kemenkes Bengkulu, 2026)
The WHO developed the AWaRe classification to support antimicrobial stewardship through standardized evaluation of antibiotic use. Several countries, including Indonesia, have implemented AWaRe classifications tailored to national clinical needs and policy priorities. However, these adaptations may lead to variations in the interpretation of antibiotic use indicators and stewardship performance. A literature search was conducted through the PubMed and ScienceDirect databases and other relevant databases with the keywords “AWaRe classification”, “antibiotic use evaluation”, “WHO”, and “Indonesia”, combined with the Boolean operators “AND” and “OR